2022
DOI: 10.1038/s41420-021-00791-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rac1 attenuates radiation-induced lung injury while suppresses lung tumor in mice

Abstract: The lung is one of the most sensitive tissues to ionizing radiation, thus, radiation-induced lung injury (RILI) stays a key dose-limiting factor of thoracic radiotherapy. However, there is still little progress in the effective treatment of RILI. Ras-related C3 botulinum toxin substrate1, Rac1, is a small guanosine triphosphatases involved in oxidative stress and apoptosis. Thus, Rac1 may be an important molecule that mediates radiation damage, inhibition of which may produce a protective effect on RILI. By es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Conversely, inhibiting N-cadherin-based polarization via NSC could decrease such structural integrity, inhibit small metastatic bodies from surviving within the body to re-embed elsewhere [10], and even convert solid tumors and spheroids into disaggregated single cells, as our results demonstrate. Indeed, prior works already demonstrated that NSC treatment effectively decreased the transendothelial migration of prostate cancer cells, suppressed lung tumors, and reduced cancer cell retention in bones [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inhibiting N-cadherin-based polarization via NSC could decrease such structural integrity, inhibit small metastatic bodies from surviving within the body to re-embed elsewhere [10], and even convert solid tumors and spheroids into disaggregated single cells, as our results demonstrate. Indeed, prior works already demonstrated that NSC treatment effectively decreased the transendothelial migration of prostate cancer cells, suppressed lung tumors, and reduced cancer cell retention in bones [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…For the orthotopic lung cancer model, MSLN-LLC cells suspended in Matrigel were injected into the left lungs of mice [ 38 40 ]. On the 7th day post injection, the mice were randomly divided into four groups: PBS, 293-Exo, CAR-Exo, and PTX@CAR-Exo.…”
Section: Methodsmentioning
confidence: 99%